Assessment of knowledge, attitude and practice of WASH and nutrition in a human-made emergency: A study on Rohingya community living in the camps of Bangladesh - Md. Azizul Haque, Prof. Dr. Sourab Chakraborty, Md. Shahoriar Ahmed (International Journal of Advanced Science and Technology, 2020)
Background: The refugees are living in vulnerable conditions where the WASH and nutrition status have declined and in jeopardy because of huge influx of them in a small area within a short period of time. Pure water, personal hygene along with basic needs like sanitation, shelter are the most vital human needs in an emergency situation. Objective: The aims of this study is to assess the knowledge and practices of water, sanitation, hygiene and nutrition by Rohingya refugees (especially mothers) living in an emergency in Bangladesh. Methodology: This is a cross-sectional, survey study and data were collected by convenient sampling technique of 995 households using face-to-face interviews. Result: The study found most vulnerable gender is female 836 (84%), age group (21-30) is 406 (40.13%), religion is 992 (99.7%), occupation is houisewife 803 (80.7%), illiterate 792 (79.6%). 68.7% (n=684) respondents in the study area reported that their drinking water comes from shallow tube well. Most of the respondents (86.5%, n=861) treat the water before drinking. Most of the respondents were unaware of the preparation method of ORS (63.9%, n= 636). Most of the respondents (87.6%, n= 872) in the study area said that they have the facility of latrines. Among households (3.2%, n=28) do not use latrines regularly. Most of the respondent (75.3 %, n= 657) responded that their children use the latrine. A total of 971 respondents, the most (78.1%, n= 758) replied that they use soap to wash their hands, whereas a considerable number of respondents (21.9%, n=213) don’t use soap. Conclusion: Without having drinking water and mass awareness about personal hygiene it could not be possible to eradicate diarrhoea, cholera and other disease outbreaks in the Rohingya and refugeecamps in Bangladesh.